Enterprise-wide strategic management : achieving sustainable success through leadership, strategies, and value creation - Rainey, David L., 1946- (Cambridge, UK : Cambridge University Press, 2010)
'In today's highly competitive and dynamic business environments, corporations can no longer afford to rely on the static strategic management constructs of the past. Enterprise-wide Strategic Management is a leading-edge work that shows how business leaders can take better advantage of their opportunities by taking a broader perspective of the world in which they operate. David Rainey advocates a holistic approach to the business environment, arguing that managers must work with all stakeholders, both internal and external, to create long-term success. Including numerous case studies featuring global corporations and small- and medium-sized enterprises (SMEs), the book provides guidance and support in formulating, developing, and implementing business strategies and action plans. It also includes advice on how to develop and deploy strategic management systems, management constructs, and organizational structures. This gives executives, strategic leaders, professionals, and practitioners the tools they need to create value and achieve sustainable success'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Strategic planning; Leadership